Evaluation of a sound environment intervention in an ICU: A feasibility study. Issue 2 (March 2018) - Johansson, Lotta; Lindahl, Berit; Knutsson, Susanne; Ögren, Mikael; Persson Waye, Kerstin; Ringdal, Mona
Abstract: Background: Currently, it is well known that the sound environment in intensive care units (ICU) is substandard. Therefore, there is a need of interventions investigating possible improvements. Unfortunately, there are many challenges to consider in the design and performance of clinical intervention studies including sound measurements and clinical outcomes. Objectives: (1) explore whether it is possible to implement a full-scale intervention study in the ICU concerning sound levels and their impact on the development of ICU delirium; (2) discuss methodological challenges and solutions for the forthcoming study; (3) conduct an analysis of the presence of ICU delirium in the study group; and (4) describe the sound pattern in the intervention rooms. Methods: A quasi-randomized clinical trial design was chosen. The intervention consisted of a refurbished two-bed ICU patient room (experimental) with a new suspended wall-to-wall ceiling and a low frequency absorber. An identical two-bed room (control) remained unchanged. Inclusion criteria: Patients >18 years old with ICU lengths of stay (LoS) >48 h. The final study group consisted of 31 patients: six from the rebuilt experimental room and 25 from the control room. Methodological problems and possible solutions were continuously identified and documented. Results: Undertaking a full-scale intervention study with continuous measurements of acoustic data in an ICU is possible. However, this feasibility study demonstrated some aspects to consider before start. The randomization process and the sound measurement procedure must be developed. Furthermore, proper education and training are needed for determining ICU delirium. Conclusion: This study raises a number of points that may be helpful for future complex interventions in an ICU. For a full-scale study to be completed a continuously updated cost calculation is necessary. Furthermore, representatives from the clinic need to be involved in all stages during the project.